Recombination pathways in a BeO yielding two main dosimetric TL peaks. (February 2022) - Konstantinidis, P.G.; Tsoutsoumanos, E.; Polymeris, G.S.; Kitis, G.
Abstract: Apart from the commercially used Thermalox, BeOR is a new type of Beryllium Oxide fabricated by a different company in Turkey. As it is shown by other groups, this dosimeter yields two overlapping main dosimetric TL peaks in the temperature region of 100–300 °C and one peak at 350 °C. The aim of the present study is the calculation of the activation energies of these two peaks with the use of specific protocols, including the Fractional Glow Technique (FGT), an Isothermal Decay signal (PID) and the Peak Shape Methods (PSM). Also, these experimental procedures were conducted in two different readers, namely the Harshaw and the Risø reader, for better repeatability and in order to minimize the error of the calculations. Moreover, another goal is to correlate the activation energy values with the recombination pathways that are present in the BeOR and its corresponding peaks. Specifically, both peaks have activation energies around 1–1.3 eV in most cases, although there are some kinds of indications for a difference in the pathways, as the high-temperature region TL main peak seems to follow the localized recombination via tunneling, in contrast with the low-temperature region TL main peak which sticks to the delocalized model with the passing via the conduction band. Highlights: A new type of BeO with two overlapping peaks at the main dosimetric region. Calculating the activation energies of the two traps using different readers. A protocol consisting of FGT, PID and PSM has been used. Localized and de-localized pathways have been observed.